Monarch’s Costume as the Means of Representation of Unity with the Population in Europe in the 17th — Early 19th Century - Skvortcova, Ekaterina A. (Actual Problems of Theory and History of Art, 2022)
The paper examines practice of dressing a monarch of foreign dynasty in a local costume. It was characteristic mainly of composite monarchies, but also of the states not included in such formations in case rulers came from a foreign dynasty. Russian art history did not address such a problem. In European costume studies, there has been no comprehensive work summarizing the existing conclusions concerning traditions of particular countries. The present paper partly fills this gap and sheds light on common mechanisms and nuances in differences on the example of the kingdom of Hungary as a part of Habsburg Monarchy, the kingdom of Poland as a part of personal union with Electorate of Saxony, kingdom of Scotland as a part of Great Britain, and Spain under the Bourbon dynasty.In each case, the costume and the practice had certain specifics: this could be the dress of the elite principally different from that of other population (Poland), or the dress of the elite similar in its cut and décor to that of other population (Hungary), or the dress of the lower classes adopted by the elite (Spain), or the dress of the lower classes not used by them from certain moment and borrowed by the elite (Scotland). However, this is always the dress associated with identity, having long history, true or invented, and still worn by the elite at the moment. The practice was conveyed in various media. One of the most important among them is a ceremonial portrait. Its rhetoric corresponds to publicity of the very act of wearing such a dress which was usually used for coronation (Poland, Hungary) or during significant festivities (Scotland).The reported study was funded by the Russian Science Foundation, project number 21-78-00067 URL: https://rscf.ru/project/21-78-00067/.
Keywords: national costume; representation of power; composite monarchy; European art of the 17th — early 19th centuries; portrait of a monarch; ceremonial portrait